Health literacy associates with clinical, treatment and work status in people with inflammatory arthritis: results from a national cohort - Mrinalini Dey; Sam Norton; Andrew Cope; Maya Buch; Richard Osborne; James Galloway; Elena Nikiphorou (Clinical Medicine)
Background: Health literacy (HL) has been deemed central to preventing and controlling non-communicable diseases by the WHO. The association between HL, other social determinants of health and outcomes in people with inflammatory arthritis (IA) remains poorly understood.We aimed to determine the association between HL and social determinants of health, clinical and non-clinical outcomes in people with IA, recruited to the National Early Inflammatory Arthritis Audit (NEIAA) in England. Methods: Patients with a confirmed IA diagnosis were identified from NEIAA and invited to complete a survey via an online platform (March–May 2024), comprising: the nine-dimension Health Literacy Questionnaire (HLQ); Work Productivity and Activity Impairment questionnaire; Generalised Anxiety Disorder (GAD-2) and Patient Health Questionnaire (PHQ-2); sociodemographics, including employment, education and marital status; disease-modifying anti-rheumatic drugs (DMARDs); self-reported disease activity, tender and swollen joint counts. The nine domains of HLQ are described in Table 1.The survey was distributed to 3,300 individuals, with those responding matched with original records within the NEIAA. Multivariable linear or logistic regression analyses, adjusting for age and gender, were conducted to determine associations between each of the HLQ domains, and socioeconomic and clinical variables. Results: A total of 995 patients with IA were included, with a median age of 59 years (IQR 50–67); 66% were women (Table 1).HL, across all domains, was associated with higher self-reported disease activity, more severe joint pain and stiffness, and greater anxiety and depression (GAD-2 and PHQ-2; Table 2).High HL in the HPS domain (OR 1.47 (1.0 –2.09)) and low HL in the FHI (OR 0.55 (0.40–0.76)) and UHI (OR 0.62 (0.44–0.88)) domains were associated with increased corticosteroid use. High HL in SS (OR 1.48 (1.03–2.13)) and AE (OR 1.30 (1.03–1.65)) domains were associated with conventional synthetic DMARD use. High HL in the HPS domain was associated with taking a biologic or targeted-synthetic DMARD (OR 1.70 (1.28–2.25)).High HL in FHI (OR 1.44 (1.10–1.88)) and UHI (OR 1.38 (1.04 – 1.84)) domains was associated with increased likelihood of employment. Overall, low HL was associated with greater absenteeism, presenteeism and work productivity loss. Only low HL in the UHI domain (b -0.15 (-0.25 to -0.05)) was associated with greater comorbidity burden.Adjusting for education did not alter outcomes. Conclusions: Low HL is associated with poorer physical and mental health, decreased likelihood of being on immune-modulating treatment, poorer work outcomes and greater comorbidity burden in IA.Our study is the largest and richest IA cohort to date to explore HL in granular detail, using a robust and validated tool (HLQ). Our results highlight the unmet need to actively assess and account for HL in the management of patients, in line with WHO’s public health strategy.